2002
DOI: 10.4049/jimmunol.169.8.4604
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Allergen-Induced Tissue Eosinophilia and Markers of Repair and Remodeling in Human Atopic Skin

Abstract: Several in vitro studies suggest that eosinophils may play a role in fibrosis, remodeling, and repair processes associated with IgE-mediated hypersensitivity. However, the relationship in vivo, between allergen-induced tissue eosinophilia and markers of repair has yet to be established in human atopic subjects. Using the allergen-induced cutaneous late-phase reaction as a model of allergic inflammation, we have tested the hypothesis that eosinophil-derived TGF-β1 and IL-13 are temporarily associated with myofi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
105
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(111 citation statements)
references
References 41 publications
5
105
1
Order By: Relevance
“…In mice, eosinophils have been implicated in bleomycin-induced pulmonary fibrosis (41) and ectopic splenic bone formation (42). In human atopic skin, eosinophil-derived TGF-␤1 was also temporally associated with myofibroblast formation and with repair and remodeling events after an allergic response (21). Thus, the roles of eosinophils and eosinophil-derived TGF-␤1 may be more diverse and profound than previously recognized.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…In mice, eosinophils have been implicated in bleomycin-induced pulmonary fibrosis (41) and ectopic splenic bone formation (42). In human atopic skin, eosinophil-derived TGF-␤1 was also temporally associated with myofibroblast formation and with repair and remodeling events after an allergic response (21). Thus, the roles of eosinophils and eosinophil-derived TGF-␤1 may be more diverse and profound than previously recognized.…”
Section: Discussionmentioning
confidence: 74%
“…Nonetheless, in the allergen challenge in human airways, the late phase airway narrowing occurs before the peak of eosinophil infiltration, and eosinophils persist after the resolution of airway narrowing (48,49). During a cutaneous allergen challenge in atopic individuals, after the peak of the late phase response, eosinophils are present in the skin (21). Thus, eosinophils and tissue eosinophilia may play a role(s) in resolving inflammation and airway reactivity and in the subsequent airway remodeling during and after the allergic response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11] In fact, eosinophil-derived transforming growth factor-β is linked with epithelial growth, fibrosis, and tissue remodeling. [12,13] Eosinophils express MHC class-II molecules, relevant co-stimulatory molecules (CD40, CD28, B7.1 and B7.2) and secrete an array of cytokines capable of promoting lymphocyte proliferation, activation and Th1 or Th2 polarization (IL-2, IL-4, IL-6, IL-12, IL-10). [11,[14][15][16][17] Further eosinophil-mediated damage is caused by toxic hydrogen peroxide and halide acids generated by EPO and by superoxide generated by the respiratory burst oxidase enzyme pathway in eosinophils.…”
Section: Function Of Eosinophilia In the Gastrointestinal Systemmentioning
confidence: 99%
“…Interestingly, the suppression by anti-IL-5 (Blyth et al 2000) or IL-5 gene deletion (Trifilieff et al 2001, Cho et al 2004) of lung tissue eosinophils was associated with an attenuation of tissue remodelling in chronic murine models of repetitive allergen challenge, and with a decrease in the content of TGF β 1 in the lung (Cho et al 2004) was observed. This has also been observed in man: here treatment with anti-IL-5 has been shown to reduce indices of tissue remodelling in allergic reactions in the skin (Phipps et al 2002) and lung . The importance of eosinophils in tissue remodelling has recently been brought into focus in GATA-1 knockout mice lacking eosinophils.…”
Section: Therapeutic Intervention To Block Eosinophil Recruitment Selmentioning
confidence: 74%